UX test in the academic information system of vocational higher education - Direstu Amalia; Dwi Cahyono; Virma Septiani; Muhammad Kristiawan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
The purpose of this study is to evaluate the user experience (UX) of academic information system (SIAKAD) using the User Experience Questionnaire (UEQ). Although SIAKAD has been running for two years, user experience testing has not yet been carried out to assess whether this application is sufficient to meet user needs or not. Questionnaires were distributed to all lecturers, administrative units, and cadets and 70 people filled out the survey. The results showed positive values on the scale of attractiveness, clarity, efficiency, accuracy, and stimulation with means > 0,8. The negative values are finding on the novelty scale where the mean is < 0,8 or 0.564. The reliability test showed that five of the six aspects were good with Cronbach-alpha > 0.7, while the UEQ weakness was on the novelty scale with an Alpha score of 0.16. A benchmark study conducts, and results shows a scale of accuracy, attractiveness, and stimulation to get an “Excellent” Product rating. Clarity and efficiency scale reach a “Good” category. Poor rating with “Below Average” obtained by novelty scale. Suggestions for further improvement is to re-evaluate the novelty aspect of SIAKAD with important points that must be considered related to innovation, invention, and creative design.